2011
DOI: 10.1088/0004-637x/737/2/66
|View full text |Cite
|
Sign up to set email alerts
|

PLANET ENGULFMENT BY ∼1.5-3MRED GIANTS

Abstract: Recent radial-velocity surveys for GK clump giants have revealed that planets also exist around ∼1.5-3 M ⊙ stars. However, no planets have been found inside 0.6 AU around clump giants, in contrast to solar-type main-sequence stars, many of which harbor short-period planets such as hot Jupiters. In this study we examine the possibility that planets were engulfed by host stars evolving on the red-giant branch (RGB). We integrate the orbital evolution of planets in the RGB and helium burning (HeB) phases of host … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
180
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(188 citation statements)
references
References 51 publications
8
180
0
Order By: Relevance
“…If this were true, the engulfment should have happened some time ago since the rotation rate is not very fast and thus the star has had time to slow down. Moreover, a putative engulfed planet should have been at a very short orbit, since for stars with M ∼ 3 M the critical initial semi-major axis for engulfment is ∼0.2-0.3 AU at the RGB phase (Villaver & Livio 2009;Kunitomo et al 2011).…”
Section: Effect Of Planet Engulfment?mentioning
confidence: 99%
See 1 more Smart Citation
“…If this were true, the engulfment should have happened some time ago since the rotation rate is not very fast and thus the star has had time to slow down. Moreover, a putative engulfed planet should have been at a very short orbit, since for stars with M ∼ 3 M the critical initial semi-major axis for engulfment is ∼0.2-0.3 AU at the RGB phase (Villaver & Livio 2009;Kunitomo et al 2011).…”
Section: Effect Of Planet Engulfment?mentioning
confidence: 99%
“…127 and NGC 2423 No. 3 using the stellar evolution code MESA (Paxton et al 2011) as was done in Kunitomo et al (2011). The evolution starts at zero-age main sequence (ZAMS) and ends before the star experiences the thermal pulses on the AGB (see Fig.…”
Section: Effect Of Planet Engulfment?mentioning
confidence: 99%
“…This observational result has been attributed to be due to the dynamical interaction between the host stars and their planets. Different authors have studied this effect, showing that close-in planets spiral inward due to the loss of orbital angular momentum, which is mainly transferred and dissipated in the stellar convective envelope (e.g., Livio & Soker, 1983;Rasio et al 1996;Sato et al 2008;Schröder & Connon Smith 2008;Villaver & Livio 2009;Kunitomo, et al 2011). As a result of the tidal decay, close-in planets are not expected to be found, at least, around post-RGB stars.…”
Section: Orbital Distributionmentioning
confidence: 99%
“…Moreover, several theoretical studies have shown that the tidal interaction between the planet and the stellar convective envelope leads to the loss of orbital angular momentum. As a result, close-in planets are expected to spiral inward and hence are subsequently engulfed by the host star (e.g., Livio & Soker 1983;Kunitomo et al 2011). However, Johnson et al (2007) showed that close-in planets are also absent around intermediate-mass subgiant stars.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the first point, the internal composition of the moons may be similar to those of the asteroid families inferred from the polluted debris. For the second point, a chain of large (moon-sized or planet-sized) bodies may help perturb an asteroid (Bonsor & Wyatt 2012) into a target as small as a white dwarf, particularly since the inner few au in white dwarf systems will have been cleared out by the increase in size of the star along the giant branch (Villaver & Livio 2009;Kunitomo et al 2011;Mustill & Villaver 2012;Adams & Bloch 2013;Nordhaus & Spiegel 2013;Villaver et al 2014;Staff et al 2016).…”
Section: Introductionmentioning
confidence: 99%